The Rule of Elections in the Islamic Jurisprudence (Islamic Sciences Journal, 2023)
Elections are among the contemporary calamities through which the head of state, ministers, governors, parliament and other positions and status are chosen through elections. Most Islamic and Arab countries have relied on elections as one of the foundations of their constitutions, and legislation from their legal and political legislations, to choose the right person to occupy public and private positions. Depending on the opinion of the electorate among the people, this is what led to the elections being considered as an important source of choosing rulers and an indispensable human right. People have a duty to implement in order to ensure their participation in political life and to occupy the highest positions in the state, hence the people's need to identify the view of Islam regarding the elections that are taking place in our country, and to demonstrate their legitimacy and the validity of participation in them or not, with regard to candidates and voters, as well as a review about the elections, their types and a history about it.
Keywords: Elections, legislation, votes, voters, candidates